1993
DOI: 10.1177/019459989310900316
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of growth rates of acoustic neuromas: Nonsurgical patients vs. subtotal resection

Abstract: A conservative approach to the management of acoustic neuromas in elderly patients has been used since 1971. Elderly patients without symptoms of brain stem compression are initially treated by observation and yearly radiographic imaging. A translabyrinthine radical-subtotal resection is performed if brain stem compression is present or if tumor is growing rapidly. Twenty-three patients, ages 65 to 86 years, had initial nonsurgical management of their tumors. Growth rates could be determined for 16 patients. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
1
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 14 publications
(1 reference statement)
6
37
1
1
Order By: Relevance
“…Partial removal did not show significant increase in the rate of tumor growth postoperatively, as stated by Rosenberg et al [11] and shown by our published results [9]. Facial nerve preservation in most elderly patients is a challenging task due to their tendency of having atherosclerotic process in feeding vessels leading to low blood perfusion to the affected area, and decreasing tissue regeneration ability.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Partial removal did not show significant increase in the rate of tumor growth postoperatively, as stated by Rosenberg et al [11] and shown by our published results [9]. Facial nerve preservation in most elderly patients is a challenging task due to their tendency of having atherosclerotic process in feeding vessels leading to low blood perfusion to the affected area, and decreasing tissue regeneration ability.…”
Section: Discussionsupporting
confidence: 73%
“…On the other hand, the risks of operating on elderly patients with short life expectancy should be taken in account, and also the effect of complications on the life quality of these patients with low functional capacity should be borne in mind. Balancing the above two opinions may lead to a higher tendency for watchful observation as these tumors have slow growth rate (\0.2 cm/year) in more than 80% of cases [2,11], making this choice safe and cost effective for asymptomatic patients. One of the drawbacks of this conservative management is the psychological impact on observed patients, as leaving a growing tumor inside skull without intervention will put some patients in continuous stress, affecting their quality of life; on the other extreme, other patients may have a false impression that no intervention means unimportant disease, thus leading to loss of follow-up as documented in some studies [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,24 The same was true when initial tumor size was used to predict growth, that is, with contradictory evidence suggested across studies. 7,18,22,23,25 However, Nikolopoulos and colleagues did assert that cystic tumors tend to have a higher growth rate (approximately 3.7 mm/year) as compared with solid tumors. Regardless, no other consistent indicators of growth were revealed across the multiple studies: not age, initial lesion size, duration of symptoms, tumor laterality, or patient sex.…”
Section: Growth Patterns and Natural Historymentioning
confidence: 99%
“…Serial neuroradiological imaging has been the subject of several publications concerning VS growth in patients who were not operated on at the time of diagnosis [1,5,14,17,19,20,24,28,29,31]. The number of tumors investigated in these studies have varied from 4 [28] to 98 [19].…”
Section: Expectancymentioning
confidence: 99%